Navigating Gamification in Language Education: Analyzing the Experiences of MA TEFL Students - Davardan, Fatemeh; Taghizadeh, Mahboubeh (International Conference on E-Learning and E-Teaching, 2025)
The research examines the experience of Iranian and Iraqi MA TEFL students about the use of digital gamification in language learning and their views of the instruction they received in this regard. Quantitative data indicated extensive daily technology use but a moderate implementation of digital games in educational settings. A gap in knowledge was observed, indicating a need for additional education. Thematic analysis of qualitative data also highlighted tools, such as Kahoot, Quizizz, and Duolingo as successful in creating enjoyable and engaging learning experiences. Nevertheless, challenges of restricted technology access, cultural opposition, and gaps in technical skills were considerable. Regardless of these disadvantages, advantages, such as boosted motivation, better retention, immediate feedback, and improved teamwork were acknowledged. The findings revealed that although digital gamification offers significant potential, thorough instruction, better infrastructure, and cultural adjustments are crucial for addressing challenges and improving language learning results.